MENINGKATKAN KESANTUNAN DALAM KOMUNIKASI AKADEMIK MAHASISWA KEPADA DOSEN MELALUI KONTEN EDUKATIF TIKTOK - Zatalini Ulvy (Media Resonansi Pengabdian Masyarakat, 2025)
The ability to communicate fluently is something students desire, both inside and outside the classroom. When communicating with lecturers, maintaining politeness is essential to avoid being judged negatively. One of the most frequently used media for formal communication is email, especially for learning purposes, asking questions, or submitting assignments. Language anxiety is one of the obstacles students face in communication, especially when using a foreign language like English. Educational content creation activity has been carried out focusing on guiding how to write emails to lecturers in English. The content created has been distributed via TikTok and received positive reactions. It has reached 14 thousand viewers, the majority of viewers are women and young students in Indonesia. There is a need for a communication guide between students and lecturers that is easily accessible to students in Indonesia to maintain politeness and prevent language anxiety.Keywords: Educative Content, TikTok, Students, Lectures, Politeness, Language Anxiety